Efficacy and safety of a nanoparticle therapeutic vaccine in patients with chronic hepatitis B: A randomized clinical trial. Issue 1 (8th December 2021) - Wei, Lai; Zhao, Tingting; Zhang, Ji; Mao, Qing; Gong, Guozhong; Sun, Yongtao; Chen, Yongping; Wang, Maorong; Tan, Deming; Gong, Zuojiong; Li, Baosen; Niu, Junqi; et al.
Abstract: Background and Aim: HBV DNA can be reduced using antiviral drugs in patients with chronic hepatitis B (CHB); however, the rate of HBeAg seroconversion remains low. A clinical trial was conducted to assess the efficacy and safety of a de novo designed liposome‐based nanoparticle lipopeptide vaccine, εPA‐44, for CHB. Approach and Results: A two‐stage phase 2 trial, which included a 76‐week, randomized, double‐blind, placebo‐controlled trial (stage 1) and a 68‐week open‐label extension (stage 2), was conducted in 15 centers across China (Clinicaltrials.gov No. NCT00869778). In stage 1, 360 human leukocyte antigen A2 (HLA‐A2)–positive and HBeAg‐positive patients were randomly and equally distributed to receive six subcutaneous injections of 600 µg or 900 µg εPA‐44 or placebo at week 0, 4, 8, 12, 20, and 28. In stage 2, 183 patients received extended 900 µg εPA‐44, and 26 patients were observed for relapse without further treatment. The primary endpoint was the percentage of patients with HBeAg seroconversion at week 76. At week 76, patients receiving 900 µg εPA‐44 achieved significantly higher HBeAg seroconversion rate (38.8%) versus placebo (20.2%) (95% CI, 6.9‐29.6%; p = 0.002). With a combined endpoint of HBeAg seroconversion, alanine aminotransferase normalization and HBV DNA < 2, 000 IU/mL, both 900 µg (18.1%) and 600 µg (14.3%), resulted in significantly higher rate versus placebo (5.0%) ( p = 0.002 and p = 0.02, respectively) at week 76. In stage 2, none (0 of 20) of 900 µg εPA‐44‐treated patients experienced serologic relapse. The safety profile of εPA‐44 was comparable to that of placebo. Conclusions: Among HLA‐A2‐positive patients with progressive CHB, a finite duration of 900 µg εPA‐44 monotherapy resulted in significantly higher HBeAg seroconversion rate than placebo and sustained off‐treatment effect. A phase 3 trial is ongoing (ChiCTR2100043708).